Shelf life prediction of dried mangoes treated with alternative anti-browning agents - Loberiano, Floridel Victoria; Acevedo, Teresita P. (1999)
Chemical kinetics of quality deterioration in relation to storage temperature was determined for prediction of shelf life dried mangoes treated with alternative anti-browning agents. storage stability was based mainly on non-enzymatic browning which suggested a zero-order reaction. A linear relationship between absorbance and color score was established indicating a good correlation between two parameters. Based on the study, alternative anti-browning agents such as sodium erythorbate, citric acid and ascorbic acid were comparable to sodium metabisulfite as browning inhibitors for dried mangoes. These antibrowning agents when added solely or in combination with other antioxidants, inhibit browning in dried mangoes to a certain extent depending on the levels used.
Thesis (M.S. Food Science)--University of the Philippines, Diliman.
Keywords: Dried mangoes -- Storage -- Philippines; Antioxidants; Chemical kinetics -- Effect of temperature on